Primitive neuroectodermal tumor in a child with Currarino syndrome - Çebi, Memnune Nur; Yılmaz, Gizem; Çelikdemir, Gökçe; Özcan, Rahşan; Ocak, Süheyla; Celkan, Tülin Tiraje; Çomunoğlu, Nil (The Turkish Journal of Pediatrics, 2022)
Background. Curarino syndrome is a rare and complex anomaly with the triad of anorectal malformation, presacral mass and sacral bone deformation. The most common cause of the presacral mass is meningioma, but teratoma is the diagnosis in about one-third of the cases. Malignant transformation of teratoma in the form of carcinoma, rhabdomyosarcoma and leukemia have previously been reported on rare occasions. Case. A 19 month-old-girl was referred with a presacral mass of 29mm x 23mm x 24mm. She was diagnosed as Currarino syndrome. The presacral mass was surgically resected and pathological examination revealed a foci of primitive neurectodermal tumor. Conclusions. This is the first case of Currarino syndrome with a primitive neuroectodermal tumor (PNET) foci in the presacral mass. Considering the risk of malignant transformation, the accurate pathological examination is important for complete systemic evaluation and treatment plan in these children.